Sistem Informasi E-recruitment Seleksi Guru (Studi Kasus Sma Katolik 1 Kabanjahe) - Hutagaol, Victor Edison; Pinem, Sanjaya (LPPM UNIKA Santo Thomas Medan, 2020)
E-recruitment Information System that can produce prospective teachers who have high competence is aim of this research. In addition to making it easier for the selection committee to find the best teacher, another advantage is data transparency, so that the results of prospective teachers obtained will be fully objective and transparent. The development of systems with rapid application development (RAD) models was chosen in developing a system built consisting of 4 stages: 1) Phase Requirement Phase, 2) Phase User Design Phase, 3) Phase Construction Phase, 4) Phase Cutover Phase. System design stages are created using unified modelling language (UML), and system implementations are created using the CodeIgniter framework. With the implementation of e-recruitment information system using rapid application development (RAD) system development model can replace manual recruitment system and can be run in organized way.